Peran Guru Bimbingan dan Konseling dalam Mengurangi Kecanduan Menonton Anime pada Siswa Kelas IX SMPN 4 Kecamatan Harau - Pratama, Nadia; Putra, Dodi Pasila (Lembaga Yasin AlSys, 2024)
Anime (アニメ) is Japanese animation drawn by hand or using computer technology. Anime is presented in spoken and moving form and can be watched through colorful pictures featuring characters in various locations and stories. Watching anime excessively also has a negative impact on students, such as running out of time to watch anime, neglecting a lot of assignments and even decreasing enthusiasm for studying because they feel too engrossed in watching anime, so they forget about study time and sleep during class hours. This research is descriptive qualitative field research, namely describing events that occur in the field or research that describes, tells and interprets a phenomenon that is developing in the present. Where this research describes the role of guidance and counseling teachers. This research uses observation, interview and documentation data collection techniques obtained from key informants and supporting informants in the field. Based on the results of research conducted by the author, the role of guidance and counseling teachers in reducing the addiction to watching anime in students is: First, implementing guidance and counseling services, namely guidance and counseling teachers, providing information services to students about the negative consequences of watching anime too often. make students addicted, Guidance and counseling teachers provide orientation and information services to students according to their condition, namely whether they are just watching or have become addicted, Guidance and counseling teachers provide individual counseling services to students who have been indicated as addicted to watching Anime and Guidance and counseling teachers collaborate with subject teachers and parents to help students solve their problems. Second, collaborate with subject teachers and collaborate with parents. The three guidance and counseling teachers have extensive knowledge or insight into the problems students are facing.